Identification of L11L and L7L as virulence-related genes in the African swine fever virus genome - Fan, Jiaqi; Zhang, Jingyuan; Wang, Fengjie; Miao, Faming; Zhang, Han; Jiang, Yiqian; Qi, Yu; Zhang, Yanyan; Hui, Lili; Zhang, Dan; Yue, Huixian; Zhou, Xintao; et al. (Frontiers in Microbiology, 2024)
Introduction African swine fever (ASF) is an infectious disease that causes considerable economic losses in pig farming. The agent of this disease, African swine fever virus (ASFV), is a double-stranded DNA virus with a capsid membrane and a genome that is 170-194 kb in length encoding over 150 proteins. In recent years, several live attenuated strains of ASFV have been studied as vaccine candidates, including the SY18ΔL7-11. This strain features deletion of L7L, L8L, L9R, L10L and L11L genes and was found to exhibit significantly reduced pathogenicity in pigs, suggesting that these five genes play key roles in virulence. Methods Here, we constructed and evaluated the virulence of ASFV mutations with SY18ΔL7, SY18ΔL8, SY18ΔL9, SY18ΔL10, and SY18ΔL11L. Results Our findings did not reveal any significant differences in replication efficiency between the single-gene deletion strains and the parental strains. Pigs inoculated with SY18ΔL8L, SY18ΔL9R and SY18ΔL10L exhibited clinical signs similar to those inoculated with the parental strains. Survival rate of pigs inoculated with 103.0TCID50 of SY18ΔL7L was 25%, while all pigs inoculated with 103.0TCID50 of SY18ΔL11L survived, and 50% inoculated with 106.0TCID50 SY18ΔL11L survived. Discussion The results indicate that L8L, L9R and L10L do not affect ASFV SY18 virulence, while the L7L and L11L are associated with virulence.